Parallelization of Microfluidic Droplet Junctions for Ultraviscous Fluids. Issue 48 (30th October 2022) - Kim, Hyeon Ho; Cho, YongDeok; Baek, Dongjae; Rho, Kyung Hun; Park, Sung Hun; Lee, Seungwoo
Abstract: The parallelization of multiple microfluidic droplet junctions has been successfully achieved so that the production throughput of the uniform microemulsions/particles has witnessed considerable progress. However, these advancements have been observed only in the case of a low viscous fluid (viscosity of 10 −2 –10 −3 Pa s). This study designs and fabricates a microfluidic device, enabling a uniform micro‐emulsification of an ultraviscous fluid (viscosity of 3.5 Pa s) with a throughput of ≈330 000 droplets per hour. Multiple T‐junctions of a dispersed oil phase, split from a single inlet, are connected into the single post‐crossflow channel of a continuous water phase. In the proposed device, the continuous water phase undergoes a series circuit, wherein the resistances are continuously accumulated. The independent corrugations of the dispersed oil phase channel, under the theoretical guidance, compromise such increased resistances; the ratio of water to oil flow rates at each junction becomes consistent across T‐junctions. Owing to the design being based on a fully 2D interconnection, single‐step soft lithography is sufficient for developing the full device. This easy‐to‐craft architecture contrasts with the previous approach, wherein complicated 3D interconnections of the multiple junctions are involved, thereby facilitating the rapid uptake of high throughput droplet microfluidics for experts and newcomers alike. Abstract : High throughput droplet microfluidics has been successfully achieved; but, only in the case of low viscous fluid (viscosity of 10 −2 –10 −3 Pa s). In this study, an easy‐to‐craft microfluidic architecture is designed and fabricated, which can be readily compatible with the high throughput generation of an ultraviscous emulsion (viscosity of 3.5 Pa s). The achieved throughput is sufficient for the fabrication of a centimeter‐scale solid‐state device comprising the microparticles (i.e., microlens array).